Heart disease - Arnold, Caroline (New York : Franklin Watts, 1990)
Describes the heart and circulatory system and both genetic and acquired diseases that can adversely affect their functioning.
Includes bibliographical references (p. 107) and index.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
7.9
7.9
Keywords: Heart -- Diseases -- Juvenile literature; Circulatory system -- Diseases; Heart -- Diseases; Cardiovascular system; Heart diseases